Diagnostic Accuracy of Urinary Reagent Strip to Determine CSF Chemistry and Cellularity (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2022)
Background: Cerebrospinal Fluid (CSF) examination is a common investigation to diagnose and evaluate different neurological diseases. The gold standard method of CSF examination is microscopy, biochemistry and culture in a standard laboratory, which require an experienced microscopist and laboratory support. Urinary reagent strip can be a point of care test in such condition. The study aimed to document the diagnostic accuracy of urinary reagent strip for the semi-quantitative analysis of CSF chemistry and cellularity.Materials and methods: One hundred hospitalized patients from the Department of Neurology, Chittagong Medical College Hospital were included in this study. CSF samples of the patients were subjected for the de nitive test (CSF microscopy and laboratory biochemical values) and the index test [Combur-10 urinary reagent strip was used as the index test for protein, glucose, leukocytes and erythrocytes. The diagnostic accuracy of each index test was calculated using different cut-off levels (Glucose 1+ vs. CSF glucose >50 mg/dL, protein 1+ vs. CSF protein >30 mg/dL, leukocyte esterase 1+ positivity vs. >10 granulocytes/mm3 and erythrocyte 1+ positivity versus >5 RBC/mm3 in CSF sample).Results: The diagnostic accuracy of protein estimation by reagent strip shows 100% sensitivity, 84.21% specificity for detection of CSF protein at level 30mg/dl. Glucose reagent strip positivity had 98.8% sensitivity and 75% specificity for detection of CSF glucose at level 50 mg/dl. Leukocyte esterase positivity by test strip had sensitivity of 60% and specificity of 100% for the detection of CSF granulocyte of >10 granulocytes/mm3. The diagnostic accuracy of erythrocyte estimation by reagent strip show 92% sensitivity, 92% specificity for detection of CSF RBC >5 cells/mm3.Conclusion: Urinary reagent strip can be used routinely for rapid analysis of CSF.A resource-limited hospital might find it useful as a point-of-care laboratory workup of CSF.Chatt Maa Shi Hosp Med Coll J; Vol.21 (2); July 2022; Page 9-13